(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Curves of Etidium Bromide binding with single and double stranded polynucleotide poly[d(A-T)]-poly[d(A-T)] were obtained in Scatchard coordinates. It was revealed that EtBr binds to double stranded poly[d(A-T)]-poly[d(A-T)] in two ways. Furthermore, EtBr may form two type complexes with one stranded poly[d(A-T)]. Values of K – binding constant and n – number site size for these complexes were obtained. Parameters of EtBr binding with single stranded and double stranded polynucleotide poly[d(A-T)J coincide with those for EtBr–B–DNA complexes.